Adoption of cloud accounting: a study on MSMEs in the Special Region of Yogyakarta Province - Dama, Arya Gading Ramdhani; Marfuah, Marfuah; Prasetyo, Priyono Puji (Proceeding International Conference on Accounting and Finance, 2026)
The purpose of this study is to find out the factors that affect the adoption of Cloud Accounting in MSMEs in the Special Region of Yogyakarta Province. This study uses a quantitative approach based on the theory of Technology Acceptance Model (TAM) and Diffusion of Innovation (DOI). The population of this study is 327,936 Micro, Small and Medium Enterprises (MSMEs) in the Special Region of Yogyakarta Province. The sample selection technique used the purposive sampling method so that 400 respondents were selected. Based on data analysis using SmartPLS.4 software, it is concluded that Coercive Pressure, Compatibility, Cost Reduction, Provider Support, Relative Advantage, Top Management Support has proven to have a significant positive effect on the adoption of Cloud Accounting in MSMEs in the Special Region of Yogyakarta Province. Likewise, Complexity and Security Concern have proven to have a significant negative effect on the adoption of Cloud Accounting in MSMEs in the Special Region of Yogyakarta Province. However, Adequate Resources, Competitive Pressure, Government Support, IT Competence, and Trading Partner Pressure have not been proven to have a significant positive effect on the adoption of Cloud Accounting in MSMEs in the Special Region of Yogyakarta Province. The results of this study have implications for MSME actors, Cloud Accounting service providers and the government. For MSME actors, the results of this study have implications in understanding the factors that must be considered when adopting Cloud Accounting. For Cloud Accounting service providers, the results of this research can be used as information to improve technical support, security, and features. The results of this research can also be the basis for training programs and government policies related to the MSME digitalization program.